Edukasi Perawatan Diri Orem Meningkatkan Kebersihan Luka Post Operasi Fraktur Ekstremitas - Balqis, Janessa Fatiha Bisma; Anjaswarni, Tri; Yuswanto, Tri Johan Agus (FORIKES, 2025)
Postoperative wound hygiene for lower extremity fractures is a key factor in preventing infection and accelerating healing. Self-care education based on Orem's Theory designed to empower patients is expected to improve independence and wound hygiene. The purpose of this study was to analyze the effect of self-care education based on Orem's Theory on postoperative wound hygiene for lower extremity fractures. This study used a pretest-posttest approach with a control group. This study involved 100 randomly selected postoperative lower extremity fracture patients. The intervention group received self-care education based on Orem's Theory, while the control group received conventional education. The research instrument was a wound hygiene observation sheet applied to both groups. The wound hygiene of the two groups was then compared. The Wilcoxon test results showed a p-value of 0.000 in the intervention group, indicating a significant improvement in wound hygiene. The proportion of patients with improved wound hygiene in the intervention group (42%) was significantly higher than in the control group (8%). The Mann-Whitney test showed a p-value of 0.000, with a mean rank of 62.00 for the intervention group and 39.00 for the control group. This study concluded that self-care education based on Orem's Theory significantly improved wound hygiene in patients with postoperative lower extremity fractures and was more effective than conventional education.Keywords: self-care education; Orem's Theory; wound hygiene; postoperative; lower extremity fractures ABSTRAK Kebersihan luka pasca operasi fraktur ekstremitas bawah merupakan faktor kunci dalam mencegah infeksi dan mempercepat penyembuhan. Edukasi perawatan diri berbasis Teori Orem yang dirancang untuk memberdayakan pasien diharapkan dapat meningkatkan kemandirian dan kebersihan luka. Tujuan penelitian ini adalah menganalisis pengaruh edukasi perawatan diri berbasis teori Orem terhadap kebersihan luka pasca operasi fraktur ekstremitas bawah. Penelitian ini menggunakan pendekatan pretest-posttest with control group. Studi ini melibatkan 100 pasien pasca operasi fraktur ekstremitas bawah yang dipilih secara acak. Kelompok intervensi menerima edukasi perawatan diri berbasis Teori Orem, sedangkan kelompok kontrol menerima edukasi konvensional. Instrumen penelitian ini adalah lembar observasi kebersihan luka yang diterapkan pada kedua kelompok. Selanjutnya kebersihan luka kedua kelompok dibandingkan. Hasil uji Wilcoxon menunjukkan nilai p 0,000 pada kelompok intervensi, yang menunjukkan adanya peningkatan kebersihan luka secara signifikan. Proporsi pasien dengan peningkatan kebersihan luka pada kelompok intervensi (42%) secara signifikan lebih tinggi dibandingkan kelompok kontrol (8%). Uji Mann-Whitney menunjukkan nilai p 0,000, dengan mean rank 62,00 untuk kelompok intervensi dan 39,00 untuk kelompok kontrol. Penelitian ini menyimpulkan bahwa edukasi perawatan diri berbasis Teori Orem secara signifikan dapat meningkatkan kebersihan luka pada pasien fraktur ekstremitas bawah pasca operasi dan lebih efektif dibandingkan edukasi konvensional.Kata kunci: edukasi perawatan diri; Teori Orem; kebersihan luka; pasca operasi; fraktur ekstremitas bawah